2023
DOI: 10.1111/1745-9133.12614
|View full text |Cite
|
Sign up to set email alerts
|

De‐prosecution and death: A reply to an imprecise and ideological critique

Abstract: In an original article, I analyzed a potential causal link between the policy of de‐prosecution in Philadelphia and an increase in homicides. Utilizing the traditional synthetic control method with extensive descriptive data and a donor pool of the other 99 largest cities in the United States, the results demonstrated a statistically significant increase of over 74 homicides per year in Philadelphia during 2015‐19 associated with de‐prosecution (p<.05). A reaction essay addressing the original article on de‐pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Likewise, Goldrosen's (2022) analysis of progressive marijuana policies on drug arrests in Brooklyn, NY, revealed that the implementation of this policy did not significantly affect marijuana possession arrest rates. 4 While Hogan (2022) uses the "progressive" classification as a proxy for de-prosecution policies, others have used this classification to identify progressive prosecutors (e.g., Foglesong et al, 2022), and his results have sparked debates about the relationship between progressive prosecutors and crime (e.g., Foglesong et al, 2022;Hogan, 2023;Kajeepeta, 2022;Kaplan et al, 2022). Therefore, it is important to consider the pros and cons associated with Hogan's (2022) classification scheme.…”
Section: E N D N O T E Smentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Goldrosen's (2022) analysis of progressive marijuana policies on drug arrests in Brooklyn, NY, revealed that the implementation of this policy did not significantly affect marijuana possession arrest rates. 4 While Hogan (2022) uses the "progressive" classification as a proxy for de-prosecution policies, others have used this classification to identify progressive prosecutors (e.g., Foglesong et al, 2022), and his results have sparked debates about the relationship between progressive prosecutors and crime (e.g., Foglesong et al, 2022;Hogan, 2023;Kajeepeta, 2022;Kaplan et al, 2022). Therefore, it is important to consider the pros and cons associated with Hogan's (2022) classification scheme.…”
Section: E N D N O T E Smentioning
confidence: 99%
“…(2022) re‐analyzed the data based on Hogan's criticism of their replication, continuing to find Philadelphia's de‐prosecution policies had no significant effect on homicide rates. Hogan (2023, p. 88) subsequently refuted these claims, arguing that Kaplan et al.’s (2022) critiques have an “ideological basis” and that once the errors in their analysis are corrected, the results show that de‐prosecution policies in Philadelphia have larger positive effects on homicides than suggested in the original article. Thus, Hogan (2023) contends that data errors in Kaplan et al.’s (2022) analysis undermine their criticism of his work.…”
Section: Prior Research On Progressive Prosecutors and Crimementioning
confidence: 99%